Nonlinear parametric studies of photon in a Fiber Bragg grating - Saktioto; Hairi, H. M.; Ali, J.; Fadhali, M.; Yupapin, P. P. (My University, 2009)
This paper describes the effect of alpha, α and gamma, γ changes to the motion of photon in a Fiber Bragg Grating. The study has been successfully performed under Bragg resonance condition where the initial frequency of the light, ω0 has the same value with the Bragg frequency, ωB. The Stokes parameter is chosen to provide important information about the total energy and energy difference between the forward and backward propagating modes. The motion of a particle moving is shown with the classic anharmonic potential where the beta, β is set to zero due to power conservation along the grating structures. © 2009 IEEE.
Keywords: Bragg resonance condition; Fiber Bragg grating; Photon; Potential energy